Co-operative surveillance cameras for high quality face acquisition in a real-time door monitoring system - Abd Manap, Nurulfajar; Mat Ibrahim, Masrullizam (IEEE, 2011)
The increasing number of CCTV cameras in use poses a problem of information overloading for end users. Smart technologies are used in video surveillance to automatically analyze and detect events of interest in real-time, through 2D and 3D video processing techniques called video analytics. This paper presents a smart surveillance stereo vision system for real-time intelligent door access monitoring. The system uses two IP cameras in a stereo configuration and a pan-tilt-zoom (PTZ) camera, to obtain real-time localised, high quality images of any triggering events.